Psychometric Evaluation of the Whiteley Index-8 in Chinese Outpatients in General Hospitals - Chen, Yixiao; Fink, Per; Wei, Jing; Toussaint, Anne-Kristin; Zhang, Lan; Zhang, Yaoyin; Chen, Hua; Ma, Xiquan; Li, Wentian; Ren, Jie; Lu, Wei; Leonhart, Rainer; et al. (Frontiers in Psychology, 2021)
Background: Excessive and persistent health anxiety is a common and disabling but often unrecognized illness. Therefore, screening patients for health anxiety is recommended in primary care. The aim of the present study was to examine the psychometric properties of an updated version of the eight-item Whiteley Index (WI-8) among outpatients in general hospitals in China. Methods: The presented data were derived from a multicenter cross-sectional study. The Chinese version of the WI-8 was administered to a total of 696 outpatients. Cronbach’s alpha was used to evaluate the internal consistency of the scale. The validity of the scale was evaluated based on factor analysis and correlation analyses. To assess the discriminant ability, receiver operating characteristic (ROC) analysis was conducted. Results: Cronbach’s alpha was 0.937, and it decreased (0.925) after deleting the new 8th item. Factor analysis extracted one factor accounting for 69.2% of the variance. Moderate correlations were found (0.414 to 0.662) between the WI-8 and General Anxiety Disorder (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Patient Health Questionnaire-15 (PHQ-15) and Somatic Symptom Disorder B-criteria (SSD-12). The ROC curve indicated excellent discriminatory ability to discriminate among patients with health anxiety (AUC=0.822). Conclusions: The new WI-8 version is a reliable and valid tool to screen for health anxiety in general hospital patients. We recommend the WI-8 as a useful screening tool for health anxiety.